Impact of Training Modules on Physicians’ Perspective of COVID-19: An Online Survey (Journal of Medicine, 2021)
Background: The outbreak of COVID-19 has remained a massive challenge for healthcare workers specially physicians. Effective professional training has a crucial role in preparing doctors for responding to pandemics.Objective: To assess the effectiveness of existing training modules on enhancing knowledge, ensuring safe practice, and improving behavior on COVID-19 among physicians.Methods: This is a descriptive, cross-sectional, online survey; where a virtual questionnaire was used to collect data through online professional platforms. A pre-tested survey tool was employed to assess the impact of professional training on infection prevention and control.Results: Total 161 physicians participated in this survey from 15 different countries. Most of the respondents (72%) received training from various sources like the workplace (60%) and international agencies (21%), through the in-person or online format. Knowledge assessment revealed advanced (43%) and competent (40%) understanding by the participants. Improving knowledge progression was displayed by the cohort who received professional training (p